(untitled) (Praxis Educativa, 2021)
The objective of this research was to know the problems faced by migrant children returned from the United States to Mexico, in their incorporation into basic education institutions. It is a qualitative research, an exploring study, carried out in five elementary schools (public and private) in the municipality of Jerez de García Salinas, Zacatecas, México, distinguished by his historical and important participation in the migration of its population to the United States, with techniques such as non-participant observation and semi-structured interview (to key indirect informants: directors, teachers, and parents of returning migrant children). The results obtained allow us to conclude that they are children who have made visible the absences that subsist in the Mexican Educational System to attend this population segment that is incorporated to the schools, to continue their schooling, already initiated in the US, highlighting as the main problems the language, teachers without training from bilingualism, the organization of special courses that favor the learning of Spanish (communication, writing and reading) for returning students, as well as training for the integration and inclusion of children return.